Development of Digital-based Minimum Competency Assessment (AKM) Type Test Instruments to Analyze Student Problem-Solving - Nurkintan Aprilia; Sigit Priatmoko; Endang Susilaningsih; Sudarmin Sudarmin; Noor Rifaan (Universitas Negeri Semarang, 2022)
The Covid-19 pandemic has given a new nuance to the world of education, learning which is usually done face-to-face has become based on digital technology. However, online learning has an unfavorable effect in improving students' literacy and numeracy skills. Both abilities are needed by students to be able to solve problems well. The purpose of this study was to develop a two-tier multiple choice complex test, Minimum Competency Assessment type, including digital-based literacy and numeracy indicators, for analyzing problem-solving students’ level 11 in reaction rate topic. This research is an R&D research with ADDIE model. The test subjects 54 students of class XI High School 1 Welahan. The instrument has been tested for content validity, construct, and reliability. Content validity tested by six expert validators, with a score of 40.83 out of a total of 44, very valid. The construct validity, and reliability were tested using Rasch model analysis. The results show, from the 20 items developed, there are 3 items that are not valid, namely number 13, 12 and 19. The reliability test showed very good results, with index value of 0.91. Digital-based test instruments are considered more practical than paper-based tests, because they make it easier to assess and provide feedback. The results of the practicality test obtained as many as 92% (50 of 54) students gave a positive response. The existence of this test instrument makes it easier for teachers to train students' problem-solving processes and analyze problem-solving abilities more quickly through the analysis of the Rasch.